Student Career Planning Through APKAS Based on Serawai Culture - Heni Sulusyawati; Anisya Sonita; Widya Kartika Sari; Susi Hardianti; Nurul Jannah (Universitas Negeri Semarang, 2025)
Technological advances have an impact on student career planning, based on the results of observations and interviews, students are still found who have not prepared their career planning thoroughly, so far student career planning has been using a manual system. With the Student Career Planning Application (APKAS) after being tested for validity and feasibility by experts, it can be declared worthy of application. The purpose of this study is to describe student career planning through APKAS based on serawai culture. This study uses a quantitative method with a descriptive approach. The population of this study were grade XII students of SMA Negeri 9 Kota Bengkulu. Sampling used proportional random sampling, with the Slovin formula. The results of this study indicate that student career planning through APKAS based on serawai culture is in the high category. This is indicated by the results of the overall percentage of 160 students, 90 students with a percentage of 56.3% are in the high category, and based on the serawai cultural tribe with a sample of 50 students, there are 28 students with a percentage of 56.00% are in the high category. This means that student career planning through APKAS based on serawai culture supports student career planning.